Who Purchases From the Informal Economy and Why? - Horodnic, Ioana Alexandra; Ciobanu, Claudia Ioana; Zaiț, Adriana; Williams, Colin C. (Frontiers in Psychology, 2022)
In recent decades scholars have acknowledged that transactions in the informal economy have not vanished with modernization and industrialisation as expected but rather remain an important contemporary aspect of overall production and consumption across the world, in both developing and developed countries. Yet little is known about the profile of the consumers in this realm or what drives them to purchase from the informal economy. A systematic review of the literature investigating consumption in the informal economy reveals a severely underdeveloped area of consumer studies with significant gaps in terms of its theoretical approaches, methods and regional coverage. The findings of the existing literature is that multiple motives are used by consumers for justifying their purchases in the informal economy beyond the dominant simplistic view that they do simply for financial gain or for a lower price (namely, it identifies social ends and failures in formal market provision in terms of availability, speed of provision and quality). The outcome is a recognition that responsibility to reducing this phenomenon with negative effects on governments, businesses, workers and consumers lies not just with public authorities but also practitioners who need to correct the failures in formal market provision. The significant gaps identified in the literature are then used to highlight a comprehensive future research agenda, which includes the need for the development of an institutionalist theoretical perspective when explaining consumers` participation in the informal economy and social marketing interventions.